Modelling of the Liquefaction Steps of Cassava Hydrolysis by Alpha-amylase using a Statistical Approach - George, George Ifeoluwa; Oladiti, Esther Oluyinka; Akram, Muhammad; Elbossaty, Walaa Fikry (European Journal of Applied Sciences, 2021)
Alpha amylase is an enzyme that has the ability to break down the hydrogen bonds that exist between molecules of starchy compounds. The enzymatic hydrolysis of cassava starch was evaluated where a suitable medium was prepared for the enzyme to work. The experiment was done at different degrees of pH values and temperatures to assess the optimal conditions for the enzyme to work. The experiment was done at degrees of 3 pH values (pH 6.0, 6.5 and 7.0); 3 temperatures (65, 70 and 75 ⁰C) and 3 times range (40, 50 and 60 min). The results showed that the p-value of the model terms for sample dry weight was significant whereas the p-values of the model terms for reducing sugar and dextrose equivalent were not significant. The R2 was found to be 94.5% for sample dry weight proved suitable for adequate representation of the actual relationship between the selected variables whereas the R2 for reducing sugar and dextrose equivalent which were 21.6 and 26.8% respectively were too low for adequate representation of the actual relationship between the selected variables. The optimal reducing sugar and dextrose equivalent were 17.84% and 14.74 DE, respectively at pH 6.5, 70 ⁰C and 60 min. The model established the actual relationship between the actual variables of the liquefaction and the predictable values of the process while the maltodextrin obtained from the modelled process may serve as a substrate to initiate a saccharification process in the production of glucose syrup.